A High‐Resolution Land Data Assimilation System Optimized for the Western United States. (12th March 2021) - Erlingis, Jessica M.; Rodell, Matthew; Peters‐Lidard, Christa D.; Li, Bailing; Kumar, Sujay V.; Famiglietti, James S.; Granger, Stephanie L.; Hurley, John V.; Liu, Pang‐Wei; Mocko, David M.
Abstract: The Western Land Data Assimilation System (WLDAS) is a custom instance of the NASA Land Information System that combines land surface parameters, meteorological forcing data, and satellite products within a land surface model to produce daily estimates of the water and energy budget variables for the western United States. WLDAS was configured through discussions with partners, with the goal of groundwater sustainability planning for the state of California in mind. The publicly available output dataset has a 1‐km grid resolution and spans 1979–present, which makes it suitable for water resources assessments. The data are also able to contextualize the recent drought events in California. Assimilation of Leaf Area Index, which is demonstrated herein to improve simulation over agricultural areas in California, specifically in terms of evapotranspiration in irrigation regions, will be included along with other data assimilation in subsequent releases of WLDAS. Abstract : Research Impact Statement : A publicly available 1‐km land data assimilation system providing daily data from 1979–present has been developed to support water resources applications in the western United States.